Synthesis of Copolymers by Ring-Opening Copolymerization of Î´-Valerolactone and 2,2-Dimethyl-1,3-Propandiol Monomers and Their Characterization - I Made Arcana; Bunbun Bundjali; M Hasan; Helen Mariani; Shinta Dewi Anggraini (Jurnal Matematika & Sains, 2008)
Copolymers of Î´-valerolactone and 2,2-dimethyl-1,3-propandiol monomers P(VL-co-DP) as raw materials in synthesisof poly(urethane-ester) were prepared by a ring-opening polymerization of 2,2-dimethyl-1,3-propandiol and Î´-valerolactone monomers in various composition using 1-hydroxy-3-chloro-tetraisobuthyldistanoxane as a catalyst.Characterizations of polymers were carried out by analysis of functional groups, microstructure, viscosity, hydroxylnumber, and also thermal properties of copolymers. The copolymers of 2,2-dimethyl-1,3-propandiol and Î´-valerolactonemonomers have a triblock chain structure, that is P(VL-block-DP-block-VL) with various chain lengths, which dependon VL/DP ratio used in copolymerization. The increase of Î´-valerolactone composition used in polymerization leads toan increase of molecular weight and melting point as well as a decrease of hydroxyl number of copolymers.